INTUITIONISTIC FUZZY α-IRRESOLUTE FUNCTIONS - Seenivasan, V.; Renuka, R. (Italian Journal of Pure and Applied Mathematics, 2014)
In this paper the concept of intuitionistic fuzzy α-irresolute functions are introduced and studied. Besides giving characterizations of these functions, several interesting properties of these functions are also given. We also study relationship between this function with other existing functions.